Entry to hospitality careers for women and beyond: Immigrant training and feminist pedagogies and practices. Issue 1 (2nd January 2020) - Shan, Hongxia; Peikazadi, Nasim; Rahemtulla, Zahida; Wilbur, Amea; Sawkins, Tanis; Goossen, Rachel
Abstract: Employment training services are provided for immigrants to integrate them into the Canadian labour market. Evaluated on short-term labour market outcomes, these programs typically focus on enhancing individuals' employability, while risking naturalizing and reproducing the dominant social and cultural order. Entry to Hospitality Careers for Women is a government-funded program based on a partnership between a community organization and a community college specialised in vocational training. Uniquely, this program aims to expand immigrant and refugee women's employment skills as well as their social and cultural spaces. A community-based partnership research project was conducted to explore how the program worked towards these goals. It finds that the program contributed to the personal development of the women, expanded their social space and enhanced their social and economic opportunities to varying degrees. It also points to a set of women-centered pedagogical and programming practices that were conductive to women's learning through the program. Firstly, as a partnership, the program leveraged the resources and expertise accrued in both the community organization and the community college. Secondly, while navigating institutional mandate, the program was oriented towards the needs of the women. Finally, the women-centered and care-based pedagogy was found to be of immediate influence on the program participants. Theoretically, this paper adds to feminist pedagogy by grounding it in the actual work of immigrant service workers, which defies any abstract attempt to fix it within the binary frame of social reproduction and transformation.